A study on the changes of China's parenting labor system from the perspective of legal culture theory (1949-1957) - Zhang, Yan; Li, Yuhong (Faculty of Social and Political Science, Universitas Airlangga, 2024)
In the early years of the founding of the People’s Republic of China (PRC), the Communist Party then referred to as CPC implemented a series of equality policies in favor of women. This type of policy is reflected in the allocation of childcare labor resources, emphasizing the construction of women’s social welfare. However, China’s women’s welfare policies are influenced by overall political decision making and exhibit an unstable state. This study discusses the changes in the CPC’s childcare norms from 1949 to 1957. Using the laws and regulations issued by the CPC government from 1949 to 1957 and the news materials published from 1949 to 1957, this study classifies and discusses these first hand historical materials in different periods using the method of literature analysis. This study uses Friedman’s legal culture theory to analyze the interaction between the internal legal culture of the government representatives of the CPC and the external legal culture of the people’s representatives. This study finds that by exploring the process of the construction of women’s welfare policy of the PRC from 1949 to 1957, it can be clearly seen that under the condition of limited financial capacity, women’s welfare work is easily abolished due to other more important national socio-economic work. From these results, this study finally concludes that women’s liberation become a tool to serve the national construction under the discourse construction of the CPC.